Implementation of Legal Protection and Human Rights for Children and Persons with Disabilities in Indonesia - Putri, Fitri Ayu Triana (International Journal of Social Research, 2025)
The protection of law and human rights (HAM) for children and persons with disabilities is a fundamental issue in inclusive social development. Although Indonesia already has a strong legal basis through Law No. 35 of 2014 concerning Child Protection and Law No. 8 of 2016 concerning Persons with Disabilities, its implementation still faces various challenges, including limited access to education, health services, and discrimination in public services. This study aims to analyze the implementation of legal protection and human rights for children and persons with disabilities in Indonesia, identify the structural barriers faced, and formulate strategies to strengthen legal protection that are more effective and inclusive. This research uses a qualitative approach with literature studies, normative analysis of applicable regulations, and secondary data processing from official institutions such as BPS, the Ministry of Social Affairs, UNICEF, and Komnas HAM. The analysis was carried out through data triangulation to identify gaps between legal regulations and factual implementation in the field. The findings of the study show that there is a significant gap in legal protection, where children without disabilities are more protected (85%) than children with disabilities (52%) and adults with disabilities (48%). The main obstacles lie in the lack of derivative regulations, budget limitations, weak coordination between agencies, and discriminatory practices in public services. This study recommends strategies to strengthen legal protection through regulatory reform, budget increases, and multi-stakeholder synergy between governments, communities, NGOs, and organizations of persons with disabilities.